Towards Efficient Ship Design: A Review of Methods and Attributes for Decision-Making in Ship Selection - Edwin Giovanny Paipa- Sanabria; George Fernández-Alonso; Daniel Gonzales Montoya; Jairo Coronado- Hernandez (Decision Making: Applications in Management and Engineering, 2025)
With the increasing sophistication of naval systems and the rising imperative for environmentally sustainable solutions, it becomes crucial to understand how multi-criteria decision-making (MCDM) models facilitate informed decision-making to ensure vessel performance and sustainability throughout their life cycle. This research undertakes a systematic literature review of MCDM applications across various stages of the ship life cycle from a systems engineering standpoint. Particular attention is given to the design phase, where MCDM approaches are employed to determine the most appropriate ship configuration, considering factors such as operational capabilities, effectiveness, and performance metrics. A total of 131 studies were examined following the PRISMA methodology, with data sourced from Scopus and the Web of Science. The review concentrated on design methodologies, hierarchical structuring, and the assessment of essential decision-making criteria, including cost, effectiveness, and risk. The results demonstrate that MCDM models not only support the identification of optimal ship configurations but also assist in evaluating their effects on operational efficiency and environmental sustainability. The study underscores the importance of incorporating a range of performance measures, including Measures of Effectiveness (MOE), Measures of Performance (MOPs), Technical Performance Measures (TPMs), and Key Performance Parameters (KPPs), to strengthen decision-making in both design and operational contexts. Finally, a framework is proposed to guide the selection of vessels that are both operationally efficient and environmentally compliant, in line with contemporary regulatory requirements.